EVALUASI PEMILIHAN ANTIBIOTIK PROFILAKSIS PADA PASIEN OPERASI SECTIO CAESAREA (SC) DI RS BETHESDA LEMPUYANGWANGI - Cristin Wiji Astuti; Jarot Yogi Hernawan; Aglita Janis Rupita (Akademi Farmasi Yarsi Pontianak, 2022)
The safety of patients is the most priority in health word. One indicator of patient safety related to medical measures is Infection in operating area. Hospital is one of the health facilities that must ensure the safety of patients from infection and support the use of antibiotics in accordance with regulations. The most operating case in Bethesda Lempuyangwangi Hospital is Sectio Caesaria (SC) surgery. Purpose of this study was to find out the apropriateness of Antibiotic profiles for Sectio caesarea (SC) surgery patients at Bethesda lempuyangwangi Hospital. This research used a descriptive design with quantitative data that was retrospective in nature. Sampling method was saturated sample in the form of a prescription for caesarean section surgery patients . The variable used is independent variable, namely the selection of prophylactic antibiotics in Sectio Caesarea (SC) surgery patients at Bethesda Lempuyangwangi Hospital by analyzed data in univariate analysis in form of a percentage. Data from 81 patients' prescriptions for Sectio Caesarea (SC) showed that the name of a drug or antibiotic prophylaxis used in Bethesda Lempuyangwangi Hospital was four namely: Cefazolin, Cefotaxime, Ceftriaxone, and Ceftazidime. Data on suitability of drug types showed as much as 35,8% accordingly and 64.2% are not appropriate. Data on suitability of dose selection in this case there were no additional oral or parenteral antibiotics showed as much as 2.46% were appropriate and 97.54% were notsuitable. Prophylactic antibiotics used in Bethesda Lempuyangwangi Hospital are availablefour namely: Cefazolin, Cefotaxime, Ceftriaxone and Ceftazidime. Appropriate type of prophylactic antibiotics based on guidelines from POGI Appropriate 35.8% (Cefazolin). Not suitable: 64.2% (Cefotaxime, Ceftriaxone, Ceftazidime). Dosage compliance (no additional oral / parenteral antibiotics). In accordance: 2.46%. Not suitable: 97.54%